Efeito da interrupção do programa de mudança de estilo de vida sobre a composição corporal de adultos portadores de componentes da síndrome metabólica - Siqueira, Muriel [UNESP]; Burini, Roberto Carlos [UNESP]; McLellan, Kátia Cristina Portero [UNESP]; Saito, Tiemi Raquel de Moraes [UNESP] (My University, 2012)
The aim of this work is to study the current lifestyle status (anthropometric indicators) of adults that participated for at least 6 months in a lifestyle modification program (MEV) "Move for Health". We conducted a cross-sectional study with 153 individuals currently away from the MEV program. Socioeconomic data and anthropometric data were assessed for all individuals. Participants were evaluated at three different moments: M0 = baseline; M1 = after 6 months of participation at MEV program; M2 = after the interruption of participation at MEV program. The statistical analysis was performed with SAS for windows, v. 9.2. Overweight was observed in 81.3% of the sample and more than half of participants evaluated presented abdominal adiposity. At the M1, it was observed body weight reduction of participants. The results suggest that the MEV program "Move for Health" is effective in improving anthropometric measurements such as waist circumference and body mass Index. MEV interventions have to be progressively and continuously, since supervision is necessary for the good results achieved by participants.

Estudar o estado atual do estilo de vida (indicadores antropométricos) de adultos com participação passada, mínima de 6 meses, no programa para mudança do estilo de vida (MEV) “Mexa-se pró-saúde”. Foi realizado um estudo transversal com 153 indivíduos participantes atualmente afastados do programa MEV. Foram levantados dados socioeconômicos e antropométricos de todos os indivíduos. Os participantes foram avaliados em três momentos distintos: M0 = início; M1 = após 6 meses de participação no programa MEV; M2 = após o desligamento do programa. A análise estatística foi realizada com auxílio do programa SAS for windows, v. 9.2. O excesso de peso foi observado em 81,3% da amostra e mais da metade dos avaliados apresentaram hiperadiposidade abdominal. No momento M1, observa-se redução de peso corporal dos participantes. Os resultados sugerem que o programa MEV “Mexa-se Pró-Saúde” é eficiente na melhora das medidas antropométricas, como circunferência abdominal e reclassificações no Índice de Massa Corporal. As intervenções de MEV têm que ser de forma progressiva e contínua, uma vez que a supervisão se faz necessária para os bons resultados conquistados.
Effects of the interruption of a lifestyle modification program on body composition of adults with metabolic syndrome components
Keywords: Metabolic syndrome; Lifestyle; Obesity; Síndrome metabólica; Estilo de vida; Obesidade